Pocahontas and the strangers - Bulla, Clyde Robert; Burchard, Peter (New York : Crowell, 1971)
A fictionalized account of the life of Pocahontas woven about the few facts known from historical records.
G2
Keywords: Pocahontas, -- Juvenile fiction